The importance of thermal history: costs and benefits of heat exposure in a tropical, rocky shore oyster - Folco Giomi; Concetta Mandaglio; Monthon Ganmanee; Guo-Dong Han; Yun-Wei Dong; Gray A. Williams; Gianluca Sar (My University, 2016)
Although thermal performance is widely recognized to be pivotal in determining species' distributions, assessment of this performance is often based on laboratory acclimated individuals, neglecting their proximate thermal history. The thermal history of a species sums the evolutionary history and, importantly, the thermal events recently experienced by individuals, including short-term acclimation to environmental variations. Thermal history is perhaps of greatest importance for species inhabiting thermally challenging environments and therefore assumed to be living close to their thermal limits, such as in the tropics. To test the importance of thermal history the responses of the tropical oyster, Isognomon nucleus, to short term differences in thermal environments were investigated. Critical and lethal temperatures and oxygen consumption were improved in oysters which previously experienced elevated air temperatures and were associated with an enhanced heat shock response, indicating that recent thermal history affects physiological performance as well as inducing short-term acclimation to acute conditions. These responses were, however, associated with trades offs in feeding activity, with oysters which experienced elevated temperatures showing reduced energy gain. Recent thermal history, therefore, seems to rapidly invoke physiological mechanisms which enhance survival to short-term thermal challenge but also longer-term climatic changes and consequently need to be incorporated into assessments of species' thermal performances.
Keywords: Rocky shore; Ostreidae; Tropical climate; Physiological and biochemical adaptations